Daughters and left-wing voting - Andrew J. Oswald; Nattavudh Powdthavee (Institute for the Study of Labor (IZA), 2006)
This paper provides evidence that daughters make people more left-wing. Having sons, by contrast, makes them more right-wing. Parents, politicians and voters are probably not aware of this phenomenon - nor are social scientists. The paper discusses its economic and evolutionary roots. It also speculates on where research might lead. The paper ends with a conjecture: left-wing individuals are people who come from families into which, over recent past generations, many females have been born.
Keywords: D1; D72; H1; J7; 330; voting; gender; daughters; political preferences; attitudes; Kinder; Geschlecht; Eltern; Wahlverhalten; Politisches Ziel; Großbritannien